Attitudes of students of teacher studies towards music education : do they change due to music lessons? - Nikolić, Lidija (Array, 2019)
This paper presents the results of research on changes in attitudes towards music education among teacher education students who were exposed to vocal-instrumental lessons over the course of two semesters. The research was conducted among second-year students of teacher education (N=103) at the Faculty of Education in Osijek, Croatia. The results have shown that students’ attitudes towards music education are relatively positive both before and after exposure to music lessons. Students with choir experience had more positive attitudes towards music education. Although positive attitudes after music lessons are somewhat higher, there is no statistically significant difference between the attitudes of students before or after music lessons. Further research on attitudes towards music education is suggested across a larger population of teacher education students, over a longer period of time, and using a wider range of instruments.